Optimizing Stunting Prevention: A Holistic Analysis of Local Government, Professional Organizations, and University Roles - Sumiaty, Sumiaty; Ramadhan, Kadar; Nurbaya, Nurbaya (Jurnal Bidan Cerdas, 2023)
Introduction: The high prevalence of stunting in Indonesia encourages the government to make various efforts to solve it, one of which is the stunting prevention convergence activity, where the village plays an important role. The implementation of this activity at the village level has not been maximized due to the weak support from various sectors involved in the region. Purpose: This study aimed to assess the role of local governments, professional organizations and universities in converging stunting prevention programs. Methods: This research will be carried out in 3 districts, namely Banggai Islands, Sigi, and Donggala. This type of research is an exploratory study. The samples of this research were village midwives and the heads of local government organizations in Banggai Laut, Sigi, Donggala, and Poso. Results: The role of local governments, professional organizations, and universities in convergence activities to prevent stunting is still not optimal. Conclusion: This research holds the potential to significantly impact stunting prevention efforts by shedding light on the collaborative dynamics among local governments, professional organizations, and universities. The outcomes of this study are expected to guide future interventions, fostering a more integrated and effective approach to stunting prevention at the village level, ultimately contributing to the reduction of stunting prevalence in the targeted districts.